2010
DOI: 10.1007/s10940-010-9126-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Clusters, Hotspots, and Spatial Intelligence: Risk Terrain Modeling as an Algorithm for Police Resource Allocation Strategies

Abstract: The study reported here follows the suggestion by Caplan et al. (Justice Q, 2010) that risk terrain modeling (RTM) be developed by doing more work to elaborate, operationalize, and test variables that would provide added value to its application in police operations. Building on the ideas presented by Caplan et al., we address three important issues related to RTM that sets it apart from current approaches to spatial crime analysis. First, we address the selection criteria used in determining which risk layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
162
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(170 citation statements)
references
References 31 publications
(17 reference statements)
4
162
0
4
Order By: Relevance
“…The risk factors are often determined and/or weighted based on a regression or some other technique to ascertain how important they are for the crime outcome to be studied, and the resulting map of a city thus shows the relative risk for crime in each of the cells the city has been divided into. RTM has been tested on different crimes, including gun violence Kennedy et al 2011), gun crime , assault , burglary (Moreto et al 2013), violence against the police (Caplan et al 2014b), and motor vehicle theft .…”
Section: Risk Terrain Modelingmentioning
confidence: 99%
“…The risk factors are often determined and/or weighted based on a regression or some other technique to ascertain how important they are for the crime outcome to be studied, and the resulting map of a city thus shows the relative risk for crime in each of the cells the city has been divided into. RTM has been tested on different crimes, including gun violence Kennedy et al 2011), gun crime , assault , burglary (Moreto et al 2013), violence against the police (Caplan et al 2014b), and motor vehicle theft .…”
Section: Risk Terrain Modelingmentioning
confidence: 99%
“…Previous studies have demonstrated that drug dealing locations tend to cluster, especially in large cities (Rengert et al 2000;Kennedy et al 2011). Nevertheless, in Bogota, these concentrations of illicit drugs sale points are increasingly combined with a constellation of scattered sale points located in peripheral areas of the city.…”
Section: Introductionmentioning
confidence: 97%
“…Figure 3 shows examples of forecasting landscapes produced for January [1][2][3][4][5][6][7]2012, for the RTM-only model (Figure 3A), the event-dependence-only model (Figure 3B), and the full model (Figure 3C), against the actual robbery occurrences during that period (white dots). Figure 3D shows for that particular week in 2012 how each model compares to the random model following the procedure described in section Model Performance.…”
Section: Spatio-temporal Event-dependencementioning
confidence: 99%
“…More recently, Caplan and Kennedy [4] proposed Risk Terrain Modeling (RTM) as a spatial analytical technique for empirical study of crime distribution. Resulting risk terrain maps show where certain crime events are statistically more likely to occur based on certain environmental vulnerabilities at micro places [4][5][6][7]. This technique considers the effects of multiple factors on creating distinct, identifiable areas that are conducive to crime, but emphasizes the importance of environmental characteristics on the attraction of motivated offenders and the emergence, persistence, and desistance of crime [4][5][6].…”
Section: Introductionmentioning
confidence: 99%